(untitled) (Panacea Journal of Medical Sciences, 2022)
Oral squamous cell carcinoma (OSCC) is the most common subtype of malignant tumor of the oral cavity. In India, oral cancer is the commonest cancer in males. Although there have been great advances in the diagnosis and treatment of OSCC in recent years, the 5-year survival rate for advanced oral cancer patients has remained approximately 20.0%.